Agricultural waste to fuel using microwave pyrolysis - Sharifah Mona, binti Abd Aziz Abdullah (2012)
:;A gricultural wastes such as palm kernel (PK) shell, wood chip (WC) and sago waste (SW) have a potential as alternative energy resources. These wastes produce abundant volatile matter which can be converted to fuel through suitable treatment such as microwave pyrolysis. A domestic microwave oven of 1000 W and 2450 MHz frequency was modified to pyrolyzed PK, WC and SW at laboratory scale. PK, WC and SW showed a maximum pyrolysis temperature at 289 °C, 280 °C (both after 5 min) and 390 °C (after 4 min) respectivel . Finding shows that the yield of bio-oils was ranged from 9-15 wt%, 6-14 wt% and 3-16 wt% for PK, WC and SW respectively. As for bio-char, the yield obtained was at 41-68 wt% (PK), 43-57 wt% (WC) and 14-53 wt% (SW). The highest calorific value recorded for bio-oils are 27.19,25.99 and 21.99 MJ/kg for PK bio-oil (PKO), WC bio-oil (WCO) and SW biooil (SWO) respectively. The GC-MS results indicated that PKO, WCO and SWO were dominated by mixture of oxygenated hydrocarbon compound. A great range of functional groups of alcohols, ketones, aldehydes and carboxylic acids were indicated in IR spectrum. The bio-char obtained from PK, WC and SW has relatively high calorific value of 29.04,24.89 and 25.99 MJ/kg respectively which is in the range with lignite and sub-bituminous coal (24-30 MJ/kg). Esterification of PKO with ethanol in the presence of sulphuric acid (as catalyst) has enhanced the quality of the bio-oil. The process has successfully improved the odour of the bio-oil to a presentable smell. The pH value increased from 3.37 to 5.09-5.12 and the calorific value increased from 27.19 to 34.78-41.52 MJ/kg.